Mind the Gap : How COVID-19 is Increasing Inequality in Latin America and the Caribbean - Clavijo, Irene; Mejía-Mantilla, Carolina; Olivieri, Sergio; Lara-Ibarra, Gabriel; Romero, Javier (World Bank, Washington, DC, 2021)
The most vulnerable households in Latin America and the Caribbean have been disproportionately affected by the Coronavirus (Covid-19) pandemic, endangering the region’s inclusive development path. High-Frequency Phone Surveys show that two months into the pandemic, in May 2020, the gaps between the most vulnerable and the least vulnerable households in terms of job loss and income loss. The uneven impacts went beyond monetary indicators, as disadvantaged households suffered from higher levels of food insecurity and had lower access to good quality health and education services, such as online sessions with a teacher. To prevent the pandemic from erasing years of progress against inequality, the most vulnerable households require short-term support to overcome their liquidity constraints via safety net transfers, thus guaranteeing that their basic needs are met. In the medium term, government efforts should be focused on the recovery of households’ primary source of income through labor market policies that actively support the placement of the less advantaged groups and improve their employability. Equally important, it is necessary to curb losses related to human capital accumulation, given the long-term consequences that this entails. The return to in-person schooling, under strict bio-security protocols, is encouraged. When not possible, schools and parents should be provided with better tools to support distance learning.